Cfd modeling of gas burners using renewable and fossil fuels - Yangaz, Murat Umut (My University, 2014)
Bu çalışmada, brülör üretimi için yaklaşımlar açıklanmış ve iki farklı brülörün hesaplamalı çözümleri verilmiştir. Parametrik bir çalışma yapılmıştır. Yakıt giriş basıncı, alev deliklerinin çap değişimi ve üç farklı gaz bileşiminin etkileri incelenmiştir. Çözümlerin sonuçları değerlendirilip birbirleriyle karşılaştırılmıştır. Aradaki farklar, emisyonlar, sıcaklıklar ile güvenli ve optimum çalışma bölgelerini içeren grafikler ve tablolar şeklinde verilmiştir. Bu çalışma endüstrinin ihtiyaç duyduğu endüstriyel brülörler için bir arayüz geliştirme kısmını da içeren daha geniş bir çalışmanın temel seviyesi olacaktır.

In this study, approaches for burner production is explained and computational solutions of two different burners are given. A parametrical study was carried out. Effects of both fuel inlet pressure, diameter change of flame holes and three different gas compositions were observed. The results of the solutions were evaluated and compared with each other. The comparison between them are given in graphs and tables of emissions, temperatures and operating conditions which consists of both safety and optimum operating zones. This study will be the ground level of a wider study which includes an interface development for industrial burners that may satisfy the industry’s need.
Keywords: Makine Mühendisliği